GLOBECOM 2020 - 2020 IEEE Global Communications Conference 2020
DOI: 10.1109/globecom42002.2020.9348030
|View full text |Cite
|
Sign up to set email alerts
|

GPS Spoofing Detector with Adaptive Trustable Residence Area for Cellular based-UAVs

Abstract: The envisioned key role of Unmanned Aerial Vehicles (UAVs) in assisting the upcoming mobile networks calls for addressing the challenge of their secure and safe integration in the airspace. The GPS spoofing is a prominent security threat of UAVs. In this paper, we propose a 5G-assisted UAV position monitoring and anti-GPS spoofing system that allows live detection of GPS spoofing by leveraging Uplink received signal strength (RSS) measurements to cross-check the position validity. We introduce the Adaptive Tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…The proposed method detects GPS spoofing attacks to some extent; however, the system experienced performance degradation during long attacks due to the interaction with the GPS sensor, especially with the Micro-Electro-Mechanical Systems sensors. In [24], a GPS spoofing detection method was proposed that leverages the uplink received signal strength measurements collected from base stations to identify the adaptive trustable residence area, which represents the trust region within which the UAV GPS position should be located to be classified as authentic or non-spoofed. In [3], the authors proposed a method for GPS spoofing attack detection based on a machine learning algorithm, Long Short-Term Memory, and compared the results to a method based on specifically designed UAV flight paths.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed method detects GPS spoofing attacks to some extent; however, the system experienced performance degradation during long attacks due to the interaction with the GPS sensor, especially with the Micro-Electro-Mechanical Systems sensors. In [24], a GPS spoofing detection method was proposed that leverages the uplink received signal strength measurements collected from base stations to identify the adaptive trustable residence area, which represents the trust region within which the UAV GPS position should be located to be classified as authentic or non-spoofed. In [3], the authors proposed a method for GPS spoofing attack detection based on a machine learning algorithm, Long Short-Term Memory, and compared the results to a method based on specifically designed UAV flight paths.…”
Section: Related Workmentioning
confidence: 99%
“…Other studies suggested countermeasures that do not rely on GPS for navigation and instead rely on the cellular network; for example in [ 14 ], the authors presented “drive me not”, a GPS spoofing detection method that utilizes mobile cellular network infrastructure to validate the position received by the GPS infrastructure. Other research [ 15 ] utilized UpLink’s received signal strength (RSS) measurements for cross-position validation for GPS spoofing detection. In another study [ 16 ], the authors built a network of clustered ground base stations (BSs) that cooperatively serve a number of UAV-UEs.…”
Section: Related Workmentioning
confidence: 99%
“…Those new standards allow the terrestrial cellular networks to provide identifying, locating, and tracking services for the UAS in order to enhance the security of the UAS operation. In this vein, the authors in [25] proposed a UAV tracking method, namely Adaptive Trustable Residence Area (ATRA), to detect the spoofed GPS position by leveraging up-link received signal strength indication. Regardless of the performance brought by the ATRA method, it requires at least three base stations at the same time.…”
Section: Introductionmentioning
confidence: 99%